Factors affecting the efficacy of attracticidal spheres for management of Drosophila suzukii (Diptera Drosophilidae). (7th December 2021) - Nixon, Laura J.; Cloonan, Kevin; Rugh, Anthony; Jones, Sharon; Evans, Breyn; Rice, Kevin; Kirkpatrick, Danielle; Short, Brent; Rodriguez‐Saona, Cesar; Leskey, Tracy C.
Abstract: Spotted‐wing drosophila, Drosophila suzukii Matsumura, is an invasive pest in the United States, Europe and South America. Females are able to oviposit in intact soft‐skinned fruit, resulting in significant economic losses due to larval feeding. Attracticidal spheres, originally developed for the apple maggot, Rhagoletis pomonella Walsh, have been used as a management tool for D . suzukii in a few studies, but little is known about their longevity as a killing device and their performance under varying pest densities. Here, we evaluated the efficacy of attracticidal spheres, containing 1% spinetoram, when stored for 6 and 12 months and when deployed to manage low (4 adults/plant), moderate (16 adults/plant) and high (64 adults/plant) density populations in blueberry and raspberry plants. Additionally, the effects of simulated (rainfall, sunlight and rainfall/sunlight combinations) and field‐based weathering for periods of 6 and 12 weeks on attracticidal spheres containing 1% thiamethoxam, fenpropathrin, spinetoram, methomyl, spinosad, dinotefuran and lambda‐cyhalothrin were evaluated. Sphere caps stored for up to 12 months yielded no significant decrease in mortality of exposed flies compared with spheres fitted with newly produced caps. For both raspberries and blueberries protected by 1% spinetoram attracticidal spheres, high relative densities of D . suzukii yielded significantly greater levels of infestation compared with moderate or low relative densities. Simulated and field‐based weathering yielded reduced fly mortality for most insecticide materials, indicating that spheres may need to be replaced at 6 weeks or less to maximize their efficacy. In general, attracticidal spheres can assist in the management of D . suzukii, but likely will not serve as a stand‐alone tool, particularly under high pest densities.